GOTONG ROYONG, TOLERANSI, DAN SOLIDARITAS SOSIAL DALAM TATANAN BUDAYA MASYARAKAT TELADAN TIMUR - Nurjannah; Annisa Pertiwi; Balqis Dwi Fadillah; Karissa Tampubolon; Mutia Rahmadani; Suci Fadilah Daulay (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mutual cooperation, tolerance, and social solidarity were chosen as research topics because these values ​​are essential foundations for maintaining harmony in multicultural communities, particularly in urban areas such as Teladan Timur Village, Medan Kota District. The diversity of ethnic, religious, and cultural backgrounds in the local community makes this study relevant to examining how local cultural values ​​persist amidst modernization. The research method used was a qualitative approach using direct observation techniques, brief interviews with residents and neighborhood heads, and documentation of community social and cultural activities. The results show that the value of mutual cooperation is still reflected in environmental cleanliness activities and community service, tolerance is evident in attitudes of mutual respect between religious communities, and social solidarity is evident through the habit of helping each other in community activities and community meetings. These findings confirm that preserving local cultural values ​​plays a crucial role in strengthening social cohesion and creating a harmonious community life.